How not to drown in a glass of water eaudiobook A novel. - Cruz, Angie (Macmillan Audio, 2022)
This program features original sound design. "Together, [narrators] Almonte and Wetherell are the key to this exceptional novel. A brilliantly narrated immigrant story, spiked with heart and flair, that will have patrons rooting for Cara's success." - Library Journal "Rossmery Almonte's pitch-perfect narration of Angie Cruz's inventive new novel transports listeners into the tumultuous, funny, heartrending world of Cara Romero...With her sibilant Spanish accent and musical intonations, Almonte's Cara is unforgettable as she launches her fierce, strong, and witty self straight into our hearts."- AudioFile Magazine "Audiobook newbie Rossmery Almonte impressively commands most of the recording as fiercely tenacious yet surprisingly charming Cara. That Almonte shares Dominican roots with both her character and author Cruz...undoubtedly enhances the expert production." - Booklist "One of my favorite books I have read in years." —Quiara Alegria Hudes, Pulitzer Prize-winning playwright and screenwriter of In the Heights From the beloved author of Dominicana , a GMA Book Club Pick and Women's Prize Finalist, an electrifying and indelible new audiobook novel about a woman who has lost everything but the chance to finally tell her story. Write this down: Cara Romero wants to work. Cara Romero thought she would work at the factory of little lamps for the rest of her life. But when, in her mid-50s, she loses her job in the Great Recession, she is forced back into the job market for the first time in decades. Set up with a job counselor, Cara instead begins to narrate the story of her life. Over the course of twelve sessions, Cara recounts her tempestuous love affairs, her alternately biting and loving relationships with her neighbor Lulu and her sister Angela, her struggles with debt, gentrification and loss, and, eventually, what really happened between her and her estranged son, Fernando. As Cara confronts her darkest secrets and regrets, we see a woman buffeted by life but still full of fight. Structurally inventive and emotionally kaleidoscopic, How Not to Drown in a Glass of Water is Angie Cruz's most ambitious and moving novel yet, and Cara is a heroine for the ages. A Macmillan Audio production from Flatiron Books.